Serum IL-23 levels in patients with vitiligo - CENGİZ, FATMA PELIN; Cengiz, FATMA PELİN; EMİROĞLU, NAZAN; Emiroglu, NAZAN; CEMIL, Bengu Cevirgen; ERDEM, Ummu Gul Bahar; KEMERIZ, Funda (My University, 2014)
Background and Design: Interleukin-23 (IL-23) is a cytokine which is believed to have an important role in the pathogenesis of autoimmune diseases. Therefore, it can be used as a target molecule in the treatment of autoimmune diseases. The aim of our study was to determine serum IL-23 levels in patients with vitiligo to understand their possible roles in the disease etiology and to compare the results with the healthy controls.